WHO IS LIABLE FOR MEDICINE CONTAINING TOXIC CHEMICALS BASED ON THE CONSUMER PROTECTION LAW - Suwinto Johan; Citra Rahayu (Institut Agama Islam Negeri (IAIN) Bone, 2023)
The relationship between producer and consumer is not limited to buying and selling transactions only. But the producer is responsible until the product usage by the consumer. The producer sells a variety of products. It might be anything from simple items to ones that risk the lives of consumers. The producer is responsible for the effects that will raise from consumption of the product. The purpose of this study is to examine the medical/medicine producer's responsibility for the impacts on consumer poisoning. The study used normative juridical research methods. The conclusion of the study is the producer must bear responsibility for contaminating manufactured medicines. The producer accountability is in the form of compensate the consumer. These things have been managed in the Consumer Protection Act. If the producer received contaminated raw materials from the suppliers, so the producer can send these raw materials back to the supplier. A fraud penalty may be imposed on the supplier if they mix or provide the incorrect kind of raw material that doesn't fit the order. However, the producer still got to send these raw materials back.